Figuring out how to Reconfigure African Studies - Seesemann, Rüdiger; Institute of African Studies (Institute of African Studies, 2020)
This Working Paper is the revised transcript of the New Year Lecture by the dean of the Africa Multiple Cluster of Excellence at the University of Bayreuth, which won the coveted funding of the Excellence Strategy of the German Federal and State Government. The agenda of reconfiguring African Studies features not only in the lecture title, but is also prominent in the cluster's agenda. However, drafting a successful proposal is one thing; implementing the agenda is another. The paper explores the various layers, levels, and intricacies implied in the reconfiguration of African Studies, and also highlights the conceptual shift required to steer the study of Africa in new directions.
Keywords: Islam; Cluster of Excellence Africa Multiple; Reconfiguration; African Studies; knowledge production; Islamic Studies; Islamic knowledge